Preliminary assessment of hazelnut shell biomass as a raw material for pellet production. (1st February 2023) - Solís, Arnaldo; Rocha, Sebastián; König, Mario; Adam, Roman; Garcés, Hugo O.; Candia, Oscar; Muñoz, Robinson; Azócar, Laura
Graphical abstract: Highlights: We evaluated hazelnut shell for pellet production. HS is suitable according to their chemical properties, such as high HHV and low ash. Complicated fuel agglomeration possibly by high content of extractives and lignin. Spherical shape of particles probably also affecting negatively agglomeration. Feasible pellet production with blend of HS lower than 30% with pine sawdust. Abstract: We evaluated the use of hazelnut shell (HS) for pellet production. The investigation of chemical properties, such as the calorific value, low ash, nitrogen, sulfur and chlorine content as well as low heavy metal contents, reveals that the proposed biomass is suitable. However, fuel agglomeration is complicated possibly by some chemical (high content of extractives and lignin) and mechanical properties (spherical shape of particles). Therefore, the blend of HS with pine sawdust is examined in an iterative study, and pellet production is feasible only for percentages of HS lower than 30% in semi-industrial pelleting. The produced pellets exhibit properties compatible to those of industrial and domestic standards; however, as expected the mechanical durability and bulk density needs to be improved. Further studies to identify the optimal operating conditions for the evaluated blend can provide strategies to satisfy the projected increase in pellet demand.